Seroprevalence of Infectious Bronchitis Virus in Birds of Grenada - Sabarinath, Arathy; Sabarinath, Gopalakrishnan P.; Tiwari, Keshaw P.; Kumthekar, Sachin M.; Thomas, Derek; Sharma , Ravindra N. (International Journal of Poultry Science, 2011)
Infectious Bronchitis (IB) is one of the most important viral diseases of poultry and it causes major economic losses in the poultry industry. The present study was conducted to investigate the prevalence of antibodies for Infectious Bronchitis Virus (IBV) in birds of Grenada. Serum samples from 474 birds including free range chickens (210), broilers (172), Muscovy ducks (50), turkeys (10), rock pigeons (31) and guinea fowl (1) were collected and screened for the presence of antibodies by a flock check ELISA kit. Overall 147 sera were positive for IBV (31.01%). This study demonstrates for the first time, the prevalence of IBV in the island and the Caribbean indicating natural exposure to the virus.